Analisis Berpikir Kreatif Siswa dalam Pemecahan Soal Cerita pada Materi Pecahan Berdasarkan Jenis Kelamin - Anisa Firdaus; Ali Shodikin (JURNAL EKSAKTA PENDIDIKAN (JEP), 2022)
This research aims to explain and identify students' creative thinking skills in solving story problems on fractional material based on gender. This research method is a descriptive qualitative research. The subjects of this research were grade VII students of MTs Ma'arif Sungegeneng which included male students with high thinking ability (SPT), female students with high thinking ability (SWT), male students with moderate thinking ability (SPS), female students with moderate thinking ability. (SWS), male students with low thinking ability (SPR), female students with low thinking ability (SWR). High, medium, low skills were determined based on the results of written tests and interviews. The method of collecting information is by giving questions consisting of 3 story questions about fractions and interviews. The results of the analysis show that the creative thinking skills of male and female students are different, where female students have superior creative thinking skills than male students.